Optical film, method for manufacturing the same, and polarizing plate
Patent Information
- Application Number
- CN202180085841.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-28
- Filing Date
- 2021-12-03
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-12-03
AI Technical Summary
[0035]根据本发明,能够提供:包含具有负的固有双折射的结晶性聚合物、具有满足nx>nz>ny的折射率、且具有大的双折射的光学膜;包含具有负的固有双折射的结晶性聚合物、具有满足nx>nz>ny的折射率的光学膜的制造方法;以及具有上述的光学膜的偏振片。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004292712300000261
Abstract
Description
Technical Field
[0001] This invention relates to optical films and their manufacturing methods, as well as polarizers. Background Technology
[0002] For a long time, a technology for manufacturing membranes using resins has been proposed (Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent No. 4486854. Summary of the Invention
[0006] The problem the invention aims to solve
[0007] Sometimes, resin is used to manufacture optical films with anisotropic refractive indices. Such anisotropic optical films can be applied to display devices as, for example, reflection suppression films or viewing angle compensation films. Specifically, an optical film whose three-dimensional refractive indices nx, ny, and nz satisfy nx > nz > ny can improve display quality when viewing the display surface from an angle of tilt.
[0008] Methods for manufacturing optical films with three-dimensional refractive indices nx, ny, and nz satisfying nx > nz > ny have been known for a long time. For example, it is known to manufacture optical films satisfying nx > nz > ny by subjecting a resin film to appropriate stretching treatment. However, it has been difficult to manufacture such optical films using polymers with negative intrinsic birefringence. Furthermore, polymers with negative intrinsic birefringence generally have low mechanical strength, making it difficult to stretch them at large stretching ratios. Therefore, in conventional methods, it has been particularly difficult to obtain optical films with high birefringence.
[0009] The present invention was made in view of the above-mentioned problems, and its object is to provide: an optical film comprising a crystalline polymer having negative intrinsic birefringence, having a refractive index satisfying nx > nz > ny, and having large birefringence; a method for manufacturing the optical film comprising a crystalline polymer having negative intrinsic birefringence and having a refractive index satisfying nx > nz > ny; and a polarizer having the above-mentioned optical film.
[0010] Solution for solving the problem
[0011] The inventors conducted in-depth research to solve the above-mentioned problems. As a result, the inventors discovered that if a method including stretching a pre-stretching film containing a crystalline polymer having negative intrinsic birefringence as a negative C plate is used, the above-mentioned problems can be solved, thereby completing the present invention.
[0012] That is, the present invention includes the following contents.
[0013] [1] An optical film comprising a crystalline polymer having negative intrinsic birefringence,
[0014] The refractive index nx1 in the direction perpendicular to the thickness direction, the refractive index ny1 in the direction perpendicular to nx1 in the direction perpendicular to the thickness direction, and the refractive index nz1 in the thickness direction of the above optical film satisfy the following equation (1).
[0015] The in-plane birefringence Re / d of the above optical film satisfies the following equation (2).
[0016] nx1>nz1>ny1 (1)
[0017] Re / d≥3×10 -3 (2).
[0018] [2] The optical film according to [1], wherein the optical film is a stretched film.
[0019] [3] The optical film according to [1] or [2], wherein the optical film has a strip shape.
[0020] [4] A polarizer having a polarizing film and an optical film as described in any one of [1] to [3].
[0021] [5] According to the polarizer described in [4], the slow axis of the optical film is at an angle of 80° to 100° to the absorption axis of the polarizing film.
[0022] [6] A method for manufacturing an optical film, wherein the refractive index nx1 in the direction providing the maximum refractive index in the direction perpendicular to the thickness direction, the refractive index ny1 in the direction perpendicular to nx1 in the direction perpendicular to the thickness direction, and the refractive index nz1 in the thickness direction satisfy equation (1).
[0023] The above manufacturing method includes the following steps:
[0024] Step (i) involves preparing a pre-stretching film comprising a crystalline polymer with negative intrinsic birefringence; and
[0025] Step (ii): Stretch the pre-stretch film as described above;
[0026] The refractive index nx2 in the direction that provides the maximum refractive index in the direction perpendicular to the thickness direction, the refractive index ny2 in the direction perpendicular to nx2 in the direction perpendicular to the thickness direction, and the refractive index nz2 in the thickness direction of the above-mentioned pre-stretching film prepared in step (i) satisfy the following equation (3).
[0027] nx1>nz1>ny1 (1)
[0028] nz2<nx2≈ny2 (3).
[0029] [7] According to the method for manufacturing the optical film described in [6], step (i) includes:
[0030] Prepare a resin film comprising a crystalline polymer having negative intrinsic birefringence; and
[0031] The above-mentioned resin film is brought into contact with a solvent to obtain the above-mentioned pre-stretch film.
[0032] [8] The method for manufacturing an optical film according to [6] or [7], wherein the optical film has a single-layer structure.
[0033] [9] The method for manufacturing an optical film according to any one of [6] to [8], wherein the crystalline polymer having negative intrinsic birefringence is a polystyrene polymer.
[0034] Invention Effects
[0035] According to the present invention, it is possible to provide: an optical film comprising a crystalline polymer having negative intrinsic birefringence, having a refractive index satisfying nx > nz > ny, and having large birefringence; a method for manufacturing an optical film comprising a crystalline polymer having negative intrinsic birefringence and having a refractive index satisfying nx > nz > ny; and a polarizer having the above-described optical film. Detailed Implementation
[0036] The present invention will now be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and can be implemented in any way without departing from the scope of the claims of the present invention and its equivalents.
[0037] In the following description, unless otherwise specified, the in-plane retardation Re of the film is represented by Re = (nx - ny) × d. Furthermore, unless otherwise specified, the in-plane birefringence of the film is represented by (nx - ny), and is therefore denoted by Re / d. Furthermore, unless otherwise specified, the thickness retardation Rth of the film is represented by Rth = [{(nx + ny) / 2} - nz] × d. Furthermore, unless otherwise specified, the thickness birefringence of the film is represented by [{(nx + ny) / 2} - nz], and is therefore denoted by Rth / d. Furthermore, unless otherwise specified, the NZ coefficient of the film is represented by (nx - nz) / (nx - ny). Here, nx represents the refractive index of the direction providing the maximum refractive index in the direction perpendicular to the thickness direction of the film (in-plane direction). ny represents the refractive index of the film in the aforementioned in-plane directions perpendicular to the direction of nx. nz represents the refractive index of the film in the thickness direction. d represents the thickness of the film. Unless otherwise specified, the measurement wavelength is 550 nm.
[0038] In the following description, unless otherwise specified, a material with positive intrinsic birefringence is a material whose refractive index in the stretching direction is greater than its refractive index in the direction perpendicular to it. Therefore, unless otherwise specified, a polymer with positive intrinsic birefringence is a polymer whose refractive index in the stretching direction is greater than its refractive index in the direction perpendicular to it. Similarly, unless otherwise specified, a material with negative intrinsic birefringence is a material whose refractive index in the stretching direction is less than its refractive index in the direction perpendicular to it. Therefore, unless otherwise specified, a polymer with negative intrinsic birefringence is a polymer whose refractive index in the stretching direction is less than its refractive index in the direction perpendicular to it.
[0039] In the following description, a "strip" shape refers to a shape with a length that is 5 times or more than the width, preferably 10 times or more, specifically a film shape with a length sufficient to be rolled up for storage or transport. There is no particular upper limit to the length, but it is typically less than 100,000 times the width.
[0040] In the following description, unless otherwise specified, the orientations of elements, such as “parallel,” “perpendicular,” and “orthogonal,” may include errors within, for example, a range of ±5°, without impairing the effects of the invention.
[0041] Unless otherwise specified, in a component with multiple films, the angle formed by the optical axes (absorption axis, transmission axis, slow axis, etc.) of each film represents the angle when the film is viewed from the thickness direction.
[0042] Unless otherwise stated, “polarizer,” “circular polarizer,” “wave plate,” and “negative C plate” include not only rigid components but also flexible components such as resin films.
[0043] [1. Overview of the optical film in the first embodiment]
[0044] The optical film of the first embodiment of the present invention satisfies the combination of the following requirements (A) to (C).
[0045] Requirement (A): Contains a crystalline polymer with negative intrinsic birefringence.
[0046] Requirement (B): The refractive indices nx1, ny1 and nz1 of the optical film satisfy the following equation (1).
[0047] Requirement (C): The in-plane birefringence Re / d of the optical film satisfies the following equation (2).
[0048] nx1>nz1>ny1 (1)
[0049] Re / d≥3×10 -3 (2)
[0050] (nx1 represents the refractive index of the direction providing the maximum refractive index perpendicular to the thickness direction of the optical film. ny1 represents the refractive index of the direction perpendicular to nx1 within the direction perpendicular to the thickness direction of the optical film. nz1 represents the refractive index in the thickness direction of the optical film.)
[0051] The aforementioned optical film has been difficult to manufacture, but it can be easily manufactured using the manufacturing method of the second embodiment described later.
[0052] [2. Crystalline polymers with negative intrinsic birefringence]
[0053] The optical film of the first embodiment of the present invention comprises a crystalline polymer having negative intrinsic birefringence. A crystalline polymer means a polymer that is crystalline. A crystalline polymer means a polymer having a melting point Tm. That is, a crystalline polymer means a polymer whose melting point Tm can be observed using differential scanning calorimetry (DSC).
[0054] The optical film contains a crystalline polymer that has negative intrinsic birefringence. When stretched, the crystalline polymer with negative intrinsic birefringence can exhibit a large refractive index in a direction perpendicular to the stretching direction. When using the manufacturing method of the second embodiment described later with a crystalline polymer having negative intrinsic birefringence, the refractive index satisfying formula (1) and the birefringence satisfying formula (2) can be easily achieved.
[0055] As a crystalline polymer with negative intrinsic birefringence, a polymer containing an aromatic ring is preferred, and examples include polystyrene-based polymers. In the following description, crystalline polystyrene-based polymers are sometimes referred to as "crystalline polystyrene-based polymers".
[0056] Crystalline polystyrene polymers can be polymers of styrene monomers. Therefore, crystalline polystyrene polymers can be polymers comprising structural units (hereinafter appropriately referred to as "styrene units") having a structure formed by polymerizing styrene monomers.
[0057] Styrene monomers can be aromatic vinyl compounds such as styrene or styrene derivatives. Examples of styrene derivatives include compounds in which substituents are substituted at the benzene ring or at the α or β position of styrene.
[0058] Examples of styrene monomers include styrene, alkylstyrene, halostyrene, haloalkylstyrene, alkoxystyrene, vinyl benzoates, and their hydrogenated polymers.
[0059] Examples of alkylstyrene include methylstyrene, ethylstyrene, isopropylstyrene, tert-butylstyrene, 2,4-dimethylstyrene, phenylstyrene, vinylnaphthalene, and vinylstyrene. Examples of halostyrene include chlorostyrene, bromostyrene, and fluorostyrene. Examples of haloalkylstyrene include chloromethylstyrene. Examples of alkoxystyrene include methoxystyrene and ethoxystyrene. Among styrene monomers, styrene, methylstyrene, ethylstyrene, and 2,4-dimethylstyrene are preferred. Furthermore, one or more styrene monomers may be used.
[0060] Crystalline polystyrene polymers preferably have an isotactic or syndiotactic structure, more preferably a syndiotactic structure. A syndiotactic structure in crystalline polystyrene polymers means that the polymer's stereochemical structure is syndiotactic. A syndiotactic structure is a stereostructure in which phenyl groups, acting as side chains, are alternately positioned in opposite directions relative to the carbon-carbon bonded main chain in a Fischer projection. Compared to polystyrene polymers with an atactic structure, syndiotactic polystyrene polymers typically have a lower specific gravity and exhibit superior resistance to hydrolysis, heat, and chemicals.
[0061] The stereoregularity of crystalline styrene polymers can be determined using nuclear magnetic resonance (NMR) of isotopic carbon. 13Quantification is achieved using C-NMR (precipitation-nuclear spectroscopy). 13 Stereotactic regularity, as determined by C-NMR, can be expressed by the proportion of consecutive structural units present. Typically, for example, it is a diad / dyad when there are two consecutive structural units, a triad when there are three consecutive structural units, and a pentad when there are five consecutive structural units. In this case, crystalline styrene polymers with syndiotactic structures can have a syndiotactic stereoregularity typically of 75% or more, preferably 85% or more, based on diads (racemic diads / racemic dyads), or a syndiotactic stereoregularity typically of 30% or more, preferably 50% or more, based on pentads (racemic pentads).
[0062] Crystalline polystyrene polymers can be homopolymers or copolymers. Therefore, a crystalline polystyrene polymer can be a homopolymer of a single styrene monomer or a copolymer of two or more styrene monomers. When the crystalline polystyrene polymer is a copolymer of two or more styrene monomers, the proportion of each styrene unit relative to 100% by weight of the total crystalline polystyrene polymer is preferably 5% by weight or more, more preferably 10% by weight or more, preferably 95% by weight or less, more preferably 90% by weight or less.
[0063] Furthermore, the crystalline polystyrene polymer can also be a copolymer of one or more styrene monomers and monomers other than styrene monomers. From the viewpoint of obtaining an optical film with the desired optical properties, the proportion of styrene units contained in the crystalline polystyrene polymer is preferably 80% by weight or more, more preferably 83% by weight or more, and even more preferably 85% by weight or more.
[0064] Typically, the proportion of a particular structural unit in a crystalline polystyrene polymer is consistent with the proportion of the monomer corresponding to that structural unit relative to the total number of monomers in the crystalline polystyrene polymer. Therefore, the proportion of styrene units in a crystalline polystyrene polymer is consistent with the proportion of styrene monomers relative to the total number of monomers in the crystalline polystyrene polymer.
[0065] Crystalline styrene polymers can be manufactured, for example, by polymerizing styrene monomers in an inactive hydrocarbon solvent or in the absence of a solvent, using a titanium compound and the condensation product of water and trialkylaluminum as a catalyst (see Japanese Patent Application Publication No. 62-187708).
[0066] Crystalline polymers with negative intrinsic birefringence can be used alone or in combination of two or more in any ratio.
[0067] The weight-average molecular weight (Mw) of the crystalline polymer with negative intrinsic birefringence is preferably 130,000 or more, more preferably 140,000 or more, particularly preferably 150,000 or more, more preferably 500,000 or less, more preferably 450,000 or less, and particularly preferably 400,000 or less. Crystalline polymers with such a weight-average molecular weight (Mw) can have a high glass transition temperature (Tg), thus improving the heat resistance of optical films.
[0068] The weight-average molecular weight (Mw) of the polymer can be determined as a polystyrene equivalent by gel permeation chromatography (GPC) using 1,2,4-trichlorobenzene as the eluent.
[0069] The glass transition temperature (Tg) of the crystalline polymer having negative intrinsic birefringence is preferably 85°C or higher, more preferably 90°C or higher, and particularly preferably 95°C or higher. Using a crystalline polymer with a high glass transition temperature (Tg) in this way improves the heat resistance of the optical film. From the viewpoint of smoothly performing stretching during the manufacturing process of the optical film, the glass transition temperature of the crystalline polymer is preferably 160°C or lower, more preferably 155°C or lower, and particularly preferably 150°C or lower.
[0070] The melting point Tm of the crystalline polymer with negative intrinsic birefringence is preferably 200°C or higher, more preferably 210°C or higher, particularly preferably 220°C or higher, preferably 300°C or lower, more preferably 290°C or lower, and particularly preferably 280°C or lower. When the melting point Tm is within the above range, the crystallization of unintended crystalline polymers during the manufacture of the resin film and the generation of foreign matter caused by thermal decomposition can be suppressed. Therefore, optical films with good appearance and optical properties can be easily obtained.
[0071] The glass transition temperature (Tg) and melting point (Tm) of a polymer can be determined by the following method. First, the polymer is melted by heating, and then the molten polymer is rapidly cooled with dry ice. Next, using this polymer as a test specimen, the glass transition temperature (Tg) and melting point (Tm) of the polymer can be determined using a differential scanning calorimeter (DSC) at a heating rate of 10 °C / min (heating mode).
[0072] The crystallinity of the crystalline polymer with negative intrinsic birefringence contained in the optical film is typically high to a certain degree. Specifically, the crystallinity range is preferably 10% or more, more preferably 15% or more, and particularly preferably 30% or more. The crystallinity of the crystalline polymer can be determined by X-ray diffraction.
[0073] Typically, optical films are formed from resins containing crystalline polymers having negative intrinsic birefringence. In the following description, the resin containing the crystalline polymer is sometimes referred to as a "crystalline resin." Therefore, optical films typically contain crystalline resins, and are preferably formed from only crystalline resins. The aforementioned crystalline resins containing crystalline polymers having negative intrinsic birefringence generally have negative intrinsic birefringence. Furthermore, the crystalline resin is preferably a thermoplastic resin.
[0074] From the viewpoint of obtaining an optical film with the desired optical properties, the amount of the crystalline polymer with negative intrinsic birefringence in 100% by weight of the crystalline resin is preferably 70% by weight or more, more preferably 80% by weight or more, particularly preferably 90% by weight or more, and usually 100% by weight or less.
[0075] The crystalline resin can contain any component combined with a crystalline polymer having negative intrinsic birefringence. Examples of such components include: crystalline polymers having positive intrinsic birefringence, non-crystalline amorphous polymers, and other polymers; lubricants; layered crystalline compounds; particulates such as inorganic microparticles; stabilizers such as antioxidants, heat stabilizers, light stabilizers, weather stabilizers, ultraviolet absorbers, and near-infrared absorbers; plasticizers; colorants such as dyes and pigments; and antistatic agents. One or more of these components can be used. The amount of any component can be appropriately set within a range that does not significantly impair the effects of the invention. The amount of any component can, for example, maintain the total light transmittance of the optical film at 85% or higher.
[0076] [3. Refractive index of optical films]
[0077] The refractive indices nx1, ny1, and nz1 of the optical film of the first embodiment of the present invention satisfy formula (1). Films containing polymers with negative intrinsic birefringence generally tend to exhibit large birefringence in the thickness direction when stretched. Therefore, it has always been difficult to manufacture films containing polymers with negative intrinsic birefringence and having refractive indices satisfying formula (1). In contrast, it is unexpected for those skilled in the art that the optical film of this embodiment can contain polymers with negative intrinsic birefringence (condition (A)) and achieve refractive indices nx1, ny1, and nz1 satisfying formula (1) (condition (B)).
[0078] An optical film having refractive indices nx1, ny1, and nz1 satisfying equation (1) can appropriately change the polarization state of light passing through the optical film along the thickness direction, and also appropriately change the polarization state of light passing through the optical film along an inclined direction that is neither parallel nor perpendicular to the thickness direction. Therefore, the optical film can perform its optical function not only for light in the thickness direction, but also for light in the inclined direction. For example, if the optical film can provide a 1 / 4 wavelength phase difference for light passing through the thickness direction, it can also provide a 1 / 4 wavelength phase difference for light passing through the inclined direction. Furthermore, for example, if the optical film can provide a 1 / 2 wavelength phase difference for light passing through the thickness direction, it can also provide a 1 / 2 wavelength phase difference for light passing through the inclined direction.
[0079] [4. In-plane birefringence of optical films]
[0080] The in-plane birefringence Re / d of the optical film in the first embodiment of the present invention satisfies equation (2). Specifically, the in-plane birefringence Re / d of the optical film is typically 3.0 × 10⁻⁶. -3 The above, more preferably 3.5×10 -3 The above further optimizes the 5.0×10 -3 The above is particularly preferred, with 8.0×10⁻⁶ being the optimal value. -3 The above describes how optical films with such a large in-plane birefringence Re / d can be thinned to obtain the desired in-plane retardation. Therefore, thin optical films with appropriate in-plane retardation can be achieved. There is no particular upper limit to the in-plane birefringence Re / d of the optical film, but from the viewpoint of smooth manufacturing, 40 × 10⁻⁶ is preferred. -3 Below, 30×10 is preferred. -3 The following is a further optimization of 20×10 -3 the following.
[0081] Typically, a large stretching ratio is required to obtain a film with a large in-plane birefringence Re / d by stretching. However, films containing polymers with inherently negative birefringence tend to exhibit a large refractive index in the thickness direction when stretched. Therefore, when stretched at a large stretching ratio, a large refractive index is generated in the thickness direction, making it difficult to obtain refractive indices nx1, ny1, and nz1 that satisfy the above equation (1). Therefore, it is difficult to satisfy requirement (C) within the constraints of requirement (B), and thus it has not been realized until now. As mentioned above, it is already difficult to achieve a film that satisfies both requirements (A) and (B), so it is understandable that the combination of requirements (A) to (C) is very difficult to achieve. The optical film of this embodiment has high industrial value in providing an optical film that satisfies the combination of requirements (A) to (C), which is particularly difficult to achieve in this way.
[0082] [5. Layer structure of optical films]
[0083] Optical films can have a multilayer structure comprising multiple layers, but a single-layer structure is preferred. A single-layer structure means having only a single layer with the same composition, and not having layers with compositions different from those described above. Therefore, optical films preferably have only one layer formed from the aforementioned crystalline resin.
[0084] [6. Properties of Optical Films]
[0085] Optical films preferably have an in-plane delay within a suitable range for their application.
[0086] For example, at a measurement wavelength of 550 nm, the specific in-plane retardation Re of the optical film is preferably 100 nm or more, more preferably 110 nm or more, particularly preferably 120 nm or more, and further preferably 180 nm or less, more preferably 170 nm or less, and particularly preferably 160 nm or less. In this case, the optical film can function as a quarter-wave plate.
[0087] For example, at a measurement wavelength of 550 nm, the specific in-plane retardation Re of the optical film is preferably 245 nm or more, more preferably 265 nm or more, particularly preferably 270 nm or more, and further preferably 320 nm or less, more preferably 300 nm or less, particularly preferably 295 nm or less. In this case, the optical film can function as a half-wave plate.
[0088] Generally, an optical film having refractive indices nx1, ny1, and nz1 satisfying equation (1) represents an NZ coefficient greater than 0 and less than 1. The NZ coefficient of the optical film is represented by (nx1-nz1) / (nx1-ny1). More specifically, the NZ coefficient of the optical film is generally greater than 0.0, preferably greater than 0.1, more preferably greater than 0.15, particularly preferably greater than 0.2, and generally less than 1.0, preferably less than 0.9, more preferably less than 0.85, particularly preferably less than 0.8. When an optical film with an NZ coefficient in such a range is applied to a display device, it can effectively improve the display quality of the display device, such as viewing angle, contrast ratio, and image quality.
[0089] The thickness retardation Rth value of the optical film can be set according to the application of the optical film. Specifically, the thickness retardation Rth of the optical film is preferably -100nm or more, more preferably -50nm or more, particularly preferably -20nm or more, preferably 100nm or less, more preferably 50nm or less, and particularly preferably 20nm or less.
[0090] The value of the birefringence Rth / d along the thickness direction of the optical film can be set according to the application of the optical film. The absolute value of the birefringence |Rth / d| along the specific thickness direction of the optical film is preferably 0.01 × 10⁻⁶. -3 The above, and more preferably 0.05×10 -3 The above, and especially preferred, is 0.1×10 -3 The preferred value is 2.0 × 10⁻⁶. -3 The following, and more preferably, is 1.5 × 10 -3 The following, particularly preferred, is 1.0 × 10 -3 the following.
[0091] The retardation and NZ coefficient of the film can be determined using a phase difference meter (e.g., the AxoScan OPMF-1 manufactured by AXOMETRICS). Furthermore, the birefringence of the film can be determined by dividing the retardation by the thickness.
[0092] Crystalline polymers with negative intrinsic birefringence typically have poor mechanical strength. In contrast, the optical film of this embodiment can possess high mechanical strength. According to the inventors' research, in the manufacturing method of the second embodiment described later, by contacting the resin film with a solvent, the mechanical strength of the crystalline resin containing the crystalline polymer with negative intrinsic birefringence is improved. The mechanical strength of the optical film can be expressed, for example, by its flexibility. For example, the optical film can be bent without breaking even when bent using a mandrel with a diameter of 2 mm.
[0093] The optical film preferably has high transparency. Specifically, the total transmittance of the optical film is preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The total transmittance of the film can be measured using a UV-Vis spectrophotometer in the wavelength range of 400 nm to 700 nm.
[0094] The optical film preferably has low haze. The haze of the optical film is preferably less than 1.0%, more preferably less than 0.8%, particularly preferably less than 0.5%, and ideally 0.0%. When such an optical film with low haze is installed in a display device, it can improve the clarity of the image displayed on that display device. The haze of the film can be measured using a haze meter (e.g., NDH5000 manufactured by Nippon Denshoku Kogyo Co., Ltd.).
[0095] Optical films can contain solvents. In the manufacturing method of the second embodiment described later, the solvent can be absorbed into the film during the step of contacting the resin film with the solvent. Specifically, by contacting the resin film, all or part of the solvent absorbed into the film can penetrate into the interior of the polymer. Therefore, even if drying is performed above the boiling point of the solvent, it is difficult to easily and completely remove the solvent. Therefore, optical films can contain solvents.
[0096] Optical films are preferably stretched films. A stretched film is a film manufactured through a stretching process. Among these, optical films are preferably uniaxially stretched films. A uniaxially stretched film is a film that is actively stretched only in one direction and not actively stretched in other directions. Uniaxially stretched films can be manufactured by stretching only in one direction, thus simplifying the manufacturing process and enabling simpler manufacturing.
[0097] Optical films can be single sheets or long strips. When the optical film is long, it can be laminated with a long strip of polarizing film to continuously manufacture polarizing sheets.
[0098] The thickness of the optical film can be appropriately set according to its application. The specific thickness of the optical film is preferably 5 μm or more, more preferably 10 μm or more, particularly preferably 15 μm or more, preferably 50 μm or less, more preferably 40 μm or less, and particularly preferably 30 μm or less.
[0099] The optical film of the first embodiment described above can be manufactured by the manufacturing method of the second embodiment described later.
[0100] [7. Overview of the method for manufacturing the optical film according to the second embodiment]
[0101] In the manufacturing method of the optical film according to the second embodiment of the present invention, an optical film with refractive indices nx1, ny1, and nz1 satisfying formula (1) is manufactured. According to this manufacturing method of the second embodiment, the optical film of the first embodiment can be manufactured. Furthermore, according to the manufacturing method of the second embodiment, an optical film having birefringence Re / d in the in-plane direction that does not satisfy formula (2) can also be manufactured.
[0102] The method for manufacturing the optical film according to the second embodiment includes:
[0103] Step (i) involves preparing a pre-stretching film comprising a crystalline polymer with negative intrinsic birefringence; and
[0104] Step (ii) involves stretching the pre-stretching film.
[0105] In this manufacturing method, the refractive indices nx2, ny2 and nz2 of the pre-stretching film prepared in step (i) satisfy the following equation (3).
[0106] nz2<nx2≈ny2 (3)
[0107] (nx2 represents the refractive index of the direction providing the maximum refractive index among the directions perpendicular to the thickness direction of the film before stretching. ny2 represents the refractive index of the direction perpendicular to nx2 among the directions perpendicular to the thickness direction before stretching. nz2 represents the refractive index in the thickness direction of the film before stretching.)
[0108] In equation (3), "nx2≈ny2" indicates that the in-plane birefringence "nx2-ny2" (=Re / d) is small. Specifically, "nx2≈ny2" holds true when the in-plane birefringence "nx2-ny2" is less than the absolute value of the birefringence in the thickness direction "|{(nx2+ny2) / 2}-nz2|" (=|Rth / d|). Therefore, it can usually be determined that the pre-stretched film with in-plane birefringence Re / d (=nx2-ny2) being less than the absolute value of the birefringence in the thickness direction |Rth / d| (=|{(nx2+ny2) / 2}-nz2|) satisfies "nx2≈ny2". Generally, when the in-plane birefringence Re / d is less than the absolute value of the birefringence in the thickness direction |Rth / d|, the NZ coefficient is less than -0.5 or greater than 1.5.
[0109] The pre-stretch film prepared in step (i) contains a crystalline polymer with negative inherent birefringence. Therefore, the pre-stretch film can generally have negative birefringence characteristics. A film "having negative birefringence characteristics" means that when the film is stretched along a stretching direction, the increase in refractive index in the direction perpendicular to the stretching direction is greater than the increase in refractive index in the stretching direction. Here, the stretching direction is generally perpendicular to the thickness direction, and therefore can be an in-plane direction. Since it is an increase, the increase in refractive index is positive when the refractive index increases by stretching, and negative when the refractive index decreases by stretching. Therefore, when a pre-stretch film having refractive indices nx2, ny2, and nz2 that satisfy equation (3) is stretched in step (ii), the refractive indices nx2 and nz2 can relatively increase, and the refractive index ny2 can relatively decrease. Therefore, according to the above manufacturing method, an optical film that satisfies equation (1) can be obtained. Generally, the optical film obtained in this way can also have negative birefringence characteristics.
[0110] There are no limitations on the method for preparing the pre-stretch film, but it is preferred to prepare it by a method that includes contacting a resin film containing a crystalline polymer having negative intrinsic birefringence with a solvent. Therefore, step (i) preferably includes the steps of: preparing a resin film containing a crystalline polymer having negative intrinsic birefringence; and contacting the resin film with a solvent to obtain the pre-stretch film.
[0111] The inventors hypothesize that the mechanism by which the resin film is contacted with the solvent to obtain the film before stretching is as described below. However, the scope of the present invention is not limited to the mechanism described below.
[0112] When a resin film containing a crystalline polymer is brought into contact with a solvent, the solvent penetrates the resin film. Through the action of the penetrated solvent, micro-Brownian motion occurs within the molecules of the crystalline polymer in the film, causing the molecular chains to align. According to the inventors' research, this molecular chain alignment can promote solvent-induced crystallization of the crystalline polymer.
[0113] However, regarding the surface area of the resin film, the front and back surfaces, which serve as the main surfaces, are larger. Therefore, regarding the penetration rate of the organic solvent, the penetration rate along the thickness direction through the aforementioned front or back surfaces is greater. In this way, the orientation of the molecules of the aforementioned crystalline polymer can occur in a manner in which the polymer molecules are oriented along the thickness direction.
[0114] When the molecules of a crystalline polymer with negative intrinsic birefringence are oriented along the thickness direction, the refractive index of the film containing these molecules decreases relatively in the thickness direction and increases relatively in the in-plane direction perpendicular to the thickness direction. Therefore, a pre-stretched film is obtained with in-plane refractive indices nx2 and ny2 greater than the refractive index nz2 in the thickness direction.
[0115] [8. Preparation of the pre-stretching film (i)]
[0116] The method for manufacturing an optical film according to a second embodiment of the present invention includes a step (i) of preparing a pre-stretch film comprising a crystalline polymer having negative intrinsic birefringence. This step (i) preferably includes: preparing a resin film comprising a crystalline polymer having negative intrinsic birefringence; and contacting the resin film with a solvent to obtain the pre-stretch film.
[0117] A crystalline polymer with negative intrinsic birefringence can be the same as the crystalline polymer contained in the optical film. Therefore, the resin film can contain the same crystalline resin as the crystalline resin contained in the optical film. Furthermore, the resin film is preferably formed only of the same crystalline resin as the crystalline resin contained in the optical film.
[0118] However, the crystallinity of the crystalline polymer contained in the resin film is preferably low. Specifically, the crystallinity is preferably less than 10%, more preferably less than 5%, and particularly preferably less than 3%. When the crystallinity of the crystalline polymer contained in the resin film before contact with the solvent is low, the refractive index can be adjusted over a wide range because contact with the solvent causes a large number of crystalline polymer molecules to orient along the thickness direction.
[0119] The resin film preferably has optical isotropy. Therefore, the resin film preferably has a small in-plane birefringence Re / d and, more preferably, a small absolute value of the birefringence |Rth / d| in the thickness direction. Specifically, the in-plane birefringence Re / d of the resin film is preferably less than 0.7 × 10⁻⁶. -3 More preferably less than 0.6×10 -3Especially preferred is less than 0.5×10 -3 Furthermore, the absolute value of the birefringence in the thickness direction of the resin film, |Rth / d|, is preferably less than 0.7 × 10⁻⁶. -3 More preferably less than 0.6×10 -3 Especially preferred is less than 0.5×10 -3 Such optical isotropic resin films exhibit low orientation of the crystalline polymer molecules, essentially existing in an unoriented state. When using such optically isotropic resin films, precise control over the optical properties of the film is unnecessary, thus simplifying the manufacturing process. Furthermore, using optically isotropic resin films typically yields optical films with low haze.
[0120] The resin film preferably has a low solvent content, and more preferably no solvent. The ratio of the solvent content in the resin film to 100% of the weight of the resin film (solvent content) is preferably 1% or less, more preferably 0.5% or less, particularly preferably 0.1% or less, and ideally 0.0%. Because the amount of solvent in the resin film before contact with the solvent is small, contact with the solvent causes a large number of crystalline polymer molecules to orient along the thickness direction, thus allowing for adjustment of the refractive index over a wide range. The solvent content of the resin film can be determined by density.
[0121] The haze of the resin film is preferably less than 1.0%, more preferably less than 0.8%, even more preferably less than 0.5%, and ideally 0.0%. The lower the haze of the resin film, the easier it is to reduce the haze of the resulting optical film.
[0122] The thickness of the resin film is preferably set according to the thickness of the optical film to be manufactured. Generally, the thickness increases upon contact with a solvent. Furthermore, the thickness decreases upon stretching. Therefore, the thickness of the resin film can also be set considering the changes in thickness caused by contact with solvents as described above and by stretching.
[0123] The resin film can be a single sheet, but is preferably a strip. By using strip resin films, optical films can be manufactured continuously using a roll-to-roll method, thus effectively improving the productivity of optical films.
[0124] As methods for manufacturing resin films, solvent-free resin films are preferably obtained through injection molding, extrusion molding, compression molding, blow molding, blow forming, calendering, injection molding, compression molding, and other resin molding methods. Among these, extrusion molding is preferred from the perspective of ease of thickness control.
[0125] The preferred manufacturing conditions in the extrusion molding process are as follows: The barrel temperature (molten resin temperature) is preferably Tm or higher, more preferably Tm+20°C or higher, preferably Tm+100°C or lower, and more preferably Tm+50°C or lower. Furthermore, the cooling agent that the molten resin extruded into a film first contacts is not particularly limited, and a cast roll is typically used. The temperature of this cast roll is preferably Tg-50°C or higher, more preferably Tg+70°C or lower, and more preferably Tg+40°C or lower. When the resin film is manufactured under these conditions, a resin film with a thickness of 1 μm to 1 mm can be easily produced. Here, "Tm" represents the melting point of the crystalline polymer with negative intrinsic birefringence, and "Tg" represents the glass transition temperature of the crystalline polymer with negative intrinsic birefringence.
[0126] Step (i) preferably includes: after obtaining the resin film, contacting the resin film with a solvent. Through contact with the solvent, the refractive index of the resin film changes, resulting in a pre-stretch film having refractive indices nx2, ny2, and nz2 that satisfy equation (3).
[0127] Organic solvents are typically used as solvents. Specific types of solvents that can impregnate the resin film without dissolving the crystalline polymer it contains are examples of hydrocarbon solvents such as cyclohexane, toluene, limonene, and decalin; and carbon disulfide. One or more types of solvents can be used.
[0128] There are no restrictions on the method of contact between the resin film and the solvent. Examples of contact methods include: spraying, in which the solvent is sprayed onto the resin film; coating, in which the solvent is coated onto the resin film; and impregnation, in which the resin film is impregnated in the solvent. Among these, impregnation is preferred from the perspective of facilitating continuous contact.
[0129] The temperature of the solvent in contact with the resin film is arbitrary within the range that the solvent can maintain in a liquid state; therefore, it can be set to a range above the melting point and below the boiling point of the solvent.
[0130] The contact time is preferably 0.5 seconds or more, more preferably 1.0 second or more, and particularly preferably 5.0 seconds or more. There is no particular upper limit, for example, it can be less than 24 hours. However, since there is a tendency that the orientation process will not change much even if the contact time is extended, it is preferable to have a short contact time within the range of obtaining the desired optical properties.
[0131] Upon contact with a solvent, the refractive index of the resin film changes. This change in refractive index typically manifests as a change in birefringence Rth / d along the thickness direction. The preferred change in birefringence Rth / d along the thickness direction due to contact with the solvent is 0.1 × 10⁻⁶.-3 The above, and more preferably 0.5×10 -3 The above, and especially preferred, is 1.0 × 10 -3 The preferred value is 50.0 × 10. -3 The following, or more preferably, is 10.0 × 10 -3 The following, particularly preferred, is 5.0 × 10 -3 The change in birefringence Rth / d in the thickness direction described above represents the absolute value of the change. The specific change in birefringence Rth / d in the thickness direction is obtained by subtracting the birefringence Rth / d of the resin film (before solvent contact) from the birefringence Rth / d of the film before stretching (the film after solvent contact), and using this absolute value. Generally, the birefringence Rth / d in the thickness direction increases through contact between the resin film and the solvent.
[0132] The in-plane birefringence Re / d of a resin film can change or remain unchanged due to contact with a solvent. The change in in-plane birefringence Re / d caused by contact with a solvent is typically 0.0 × 10⁻⁶. -3 The above, preferably 0.1×10 -3 The above, and especially preferred, is 0.2×10 -3 The above is preferably 10×10 -3 The following, and more preferably, is 5×10 -3 The following, especially preferred, is 2×10 -3 The following describes the change in in-plane birefringence Re / d, where the change represents the absolute value of the change. The specific change in in-plane birefringence Re / d is determined by subtracting the in-plane birefringence Re / d of the resin film (before solvent contact) from the in-plane birefringence Re / d of the film before stretching (the film after solvent contact), using this absolute value.
[0133] As described above, by contacting the resin film with a solvent, a pre-stretch film with refractive indices nx2, ny2, and nz2 satisfying equation (3) is obtained. Equation (3) indicates that the pre-stretch film is a negative C-plate. Therefore, the refractive index nz2 in the thickness direction of the pre-stretch film is less than the refractive indices nx2 and ny2 in the in-plane direction. Furthermore, the refractive indices nx2 and ny2 in the in-plane direction of the pre-stretch film are the same or similar values. Therefore, the pre-stretch film typically has a relatively small difference between refractive indices nx2 and ny2, a relatively large difference between refractive indices nx2 and nz2, and a relatively large difference between refractive indices ny2 and nz2.
[0134] At this point, the difference between the refractive index nz2 in the thickness direction and the refractive indices nx2 and ny2 in the in-plane direction can be represented by the birefringence Rth / d in the thickness direction. That is, the birefringence Rth / d in the thickness direction of the pre-stretched film can be represented by "Rth / d = {(nx2 + ny2) / 2} - nz2", therefore, the difference between the refractive index nz2 in the thickness direction and the refractive indices nx2 and ny2 in the in-plane direction can be represented by its birefringence Rth / d. The preferred birefringence Rth / d in the thickness direction of the pre-stretched film is 0.2 × 10⁻⁶. -3 The above, and more preferably 0.5×10 -3 The above, and especially preferred, is 1.0 × 10 -3 The preferred value is 10×10. -3 The following, and more preferably, is 6.0 × 10 -3 The following, particularly preferred, is 4.0 × 10 -3 the following.
[0135] Furthermore, the difference between the in-plane refractive index nx2 and the refractive index ny2 can be represented by the in-plane birefringence Re / d. That is, the in-plane birefringence Re / d of the pre-stretched film can be represented by "Re / d = nx2 - ny2", thus the difference between the in-plane refractive index nx2 and the refractive index ny2 can be represented by its in-plane birefringence Re / d. Generally, the difference between the in-plane refractive index nx2 and the refractive index ny2 is smaller than the difference between the refractive index nz2 in the thickness direction and the in-plane refractive indices nx2 and ny2. Therefore, the in-plane birefringence Re / d of the pre-stretched film can be smaller than the value of the birefringence Rth / d in the thickness direction of the pre-stretched film. The specific range of the in-plane birefringence Re / d of the pre-stretched film is preferably 0.1 × 10⁻⁶. -3 The above, and more preferably 0.2×10 -3 The above, and especially preferred, is 0.5×10 -3 The preferred value is 5.0 × 10⁴. -3 The following, and more preferably, is 4.0 × 10 -3 The following, particularly preferred, is 3.0 × 10 -3 the following.
[0136] The pre-stretch film preferably has an NZ coefficient greater than 1.5. Specifically, the NZ coefficient of the pre-stretch film is preferably greater than 1.5, more preferably greater than 1.8, and particularly preferably greater than 2.0. There is no particular upper limit, but it is preferably less than 200, more preferably less than 100, and particularly preferably less than 50.
[0137] When a solvent is introduced into the resin film through contact with the solvent, the thickness of the resin film typically increases. Therefore, the thickness of the unstretched film obtained after solvent contact is usually thicker than the resin film. In this case, the lower limit of the thickness change rate can be, for example, 1% or more, 5% or more, or 10% or more. Furthermore, the upper limit of the thickness change rate can be, for example, 80% or less, 50% or less, or 40% or less. The aforementioned thickness change rate refers to the ratio obtained by dividing the difference between the thickness of the resin film (the film before solvent contact) and the thickness of the unstretched film (the film after solvent contact) by the thickness of the resin film.
[0138] Typically, the pre-stretch film obtained by contacting the solvent with the resin film has higher mechanical strength than the resin film before contact with the solvent. Therefore, the pre-stretch film can have excellent tensile strength, and thus is not prone to breakage even under harsh stretching conditions in process (ii). Therefore, when using the pre-stretch film obtained by contacting the resin film with the solvent, stretching at high temperatures and at high stretch ratios is possible.
[0139] [9. The process of stretching the pre-stretched film (ii)]
[0140] The method for manufacturing an optical film according to the second embodiment of the present invention includes a step (ii) of stretching a pre-stretching film after step (i). By stretching, the molecules of the polymer contained in the pre-stretching film can be oriented in a direction corresponding to the stretching direction. Therefore, the refractive index of the pre-stretching film can be adjusted according to the stretching in step (ii), and thus an optical film having the desired optical properties can be obtained.
[0141] The stretching direction is not limited and can include, for example, the length direction, the width direction, and the inclined direction. Here, the inclined direction refers to a direction perpendicular to the thickness direction and neither parallel nor perpendicular to the width direction. Furthermore, the stretching direction can be one direction or two or more directions, but one direction is preferred. Moreover, in stretching along one direction, free uniaxial stretching without applying constraint forces in directions other than the stretching direction is even more preferred. Based on these stretching methods, optical films with desired optical properties can be easily manufactured.
[0142] The pre-stretch film typically exhibits negative birefringence, thus, when stretched in one direction, an optical film with a slow axis perpendicular to that stretching direction can be obtained. Therefore, since the slow axis direction of the optical film can be adjusted according to the stretching direction, the stretching direction can also be selected based on the desired slow axis direction for the optical film to appear. Typically, a strip of polarizing film has an absorption axis in its length direction and a transmission axis in its width direction. Therefore, for example, if it is desired to obtain an optical film with a slow axis perpendicular to the absorption axis of the polarizing film, the pre-stretch film can be stretched along its length direction to obtain an optical film with a slow axis in the width direction. In this case, a polarizer can be efficiently manufactured by using a roll-to-roll configuration of a strip of optical film and a strip of polarizing film.
[0143] The stretching ratio is preferably 1.1 times or more, more preferably 1.2 times or more, preferably 20.0 times or less, more preferably 10.0 times or less, further preferably 5.0 times or less, and particularly preferably 2.0 times or less. The specific stretching ratio is expected to be appropriately set according to factors such as the optical properties, thickness, and mechanical strength of the optical film to be manufactured. When the stretching ratio is above the lower limit of the above range, a significant change in birefringence can be achieved through stretching. Furthermore, when the stretching ratio is below the upper limit of the above range, the direction of the slow axis can be easily controlled, or film breakage can be effectively suppressed.
[0144] The stretching temperature is preferably "Tg+5°C" or higher, more preferably "Tg+10°C" or higher, more preferably "Tg+100°C" or lower, and more preferably "Tg+90°C" or lower. Here, "Tg" represents the glass transition temperature of the crystalline polymer with negative intrinsic birefringence. When the stretching temperature is above the lower limit of the above range, the pre-stretch film can be sufficiently softened and stretched uniformly. Furthermore, at such a high temperature, the amount of solvent in the film can be reduced by drying. In particular, when using a pre-stretch film obtained by contacting the resin film with a solvent, the pre-stretch film has high mechanical strength and is not easily broken even by stretching at high temperatures, so it is preferable to stretch at a higher temperature for effective drying. Furthermore, when the stretching temperature is below the upper limit of the above range, the curing of the pre-stretch film caused by the crystallization of the crystalline polymer can be suppressed, so stretching can be performed smoothly. Furthermore, a large birefringence can be exhibited by stretching. In addition, the haze of the obtained optical film can generally be reduced and the transparency improved.
[0145] By performing the stretching process described above, the molecules in the film can be oriented along the stretching direction, thus changing the refractive index of the film before stretching. Therefore, an optical film with refractive indices nx1, ny1, and nz1 satisfying equation (1) can be obtained.
[0146] [10. Any process]
[0147] The manufacturing method of the optical film may further include any steps combined with the steps (i) to (ii) described above. Examples of such steps include: a step of preheating the pre-stretched film before step (ii); a step of heat-treating the optical film obtained in step (ii) to promote the crystallization of the crystalline polymer; a step of drying the optical film to reduce the amount of solvent in the film; and a step of thermally shrinking the optical film to remove residual stress in the film.
[0148] According to the manufacturing method described above, a long strip of stretchable pre-film can be used to manufacture a long strip of optical film. The method for manufacturing the optical film may include a step of winding the long strip of optical film manufactured in this way into a roll. Furthermore, the method for manufacturing the optical film may also include a step of cutting the long strip of optical film into a desired shape.
[0149] [11. Optical film manufactured by the manufacturing method of the second embodiment]
[0150] According to the manufacturing method of the second embodiment described above, an optical film having refractive indices nx1, ny1, and nz1 satisfying formula (1) can be obtained. This optical film may not have in-plane birefringence Re / d satisfying formula (2), but it is preferable to have in-plane birefringence Re / d satisfying formula (2). According to the manufacturing method of the second embodiment, it is not necessary to have in-plane birefringence Re / d satisfying formula (2), but otherwise, an optical film identical to the optical film described in the first embodiment can be obtained.
[0151] [12. Polarizing filter]
[0152] One embodiment of the polarizer of the present invention has the aforementioned optical film and polarizing film. The polarizing film typically functions as a linear polarizer. Therefore, the polarizer can transmit a portion of polarized light while blocking other polarized light.
[0153] Polarizing films typically have an absorption axis and a transmission axis perpendicular to the absorption axis. Furthermore, they are capable of absorbing linearly polarized light with a vibration direction parallel to the absorption axis and transmitting linearly polarized light with a vibration direction parallel to the transmission axis. The vibration direction of linearly polarized light refers to the vibration direction of the electric field of the linearly polarized light. In this case, the absorption axis of the polarizing film and the slow axis of the optical film are preferably at a specific angle.
[0154] In one example, the angle between the absorption axis of the polarizing film and the slow axis of the optical film is preferably 80° or more, more preferably 85° or more, particularly preferably 88° or more, preferably 100° or less, more preferably 95° or less, and particularly preferably 92° or less. In this case, the optical film preferably has an in-plane delay that allows it to function as a half-wave plate. When this polarizing film is installed in an image display device, it can be used as a polarizing film capable of compensating for viewing angle.
[0155] In another example, the angle between the absorption axis of the polarizing film and the slow axis of the optical film is preferably 40° or more, more preferably 42° or more, particularly preferably 44° or more, preferably 50° or less, more preferably 48° or less, and particularly preferably 46° or less. In this case, the optical film preferably has an in-plane retardation capable of functioning as a quarter-wave plate. The polarizer in this example can be used as a circularly polarized plate that can transmit circularly polarized light in one direction of rotation while blocking circularly polarized light in other directions of rotation. This circularly polarized plate can suppress the reflection of external light by being placed on the display surface of the display device.
[0156] Any polarizing film can be used. Examples of polarizing films include: films obtained by adsorbing iodine or dichroic dyes onto a polyvinyl alcohol film and then performing uniaxial stretching in a boric acid bath; and films obtained by adsorbing iodine or dichroic dyes onto a polyvinyl alcohol film, stretching it, and then modifying a portion of the polyvinyl alcohol units in the molecular chain into polyvinylene units. Among these, polarizing films containing polyvinyl alcohol are preferred.
[0157] When natural light is incident on the polarizing film, polarized light in only one direction will pass through. The degree of polarization of the polarizing film is not particularly limited, but is preferably 98% or higher, more preferably 99% or higher. Furthermore, the thickness of the polarizing film is preferably 5 μm to 80 μm.
[0158] The aforementioned polarizer can also contain arbitrary layers. Examples of arbitrary layers include: a polarizer protective film layer; an adhesive layer for bonding the polarizing film and the optical film; a hard coating such as an impact-resistant polymethyl methacrylate resin layer; a mat layer to improve the smoothness of the film; an anti-reflective layer; an anti-fouling layer; and an anti-static layer. These arbitrary layers can be provided as a single layer or as two or more layers.
[0159] Example
[0160] The following embodiments are provided to specifically illustrate the present invention. However, the present invention is not limited to the embodiments shown below, and can be implemented in any manner without departing from the scope of the claims and their equivalents.
[0161] In the following instructions, unless otherwise stated, "%" and "parts" refer to quantities based on weight. Furthermore, unless otherwise stated, the operations described below shall be performed under normal atmospheric conditions (23°C, 1 atmosphere).
[0162] [Methods for determining glass transition temperature Tg and melting point Tm]
[0163] The glass transition temperature (Tg) and melting point (Tm) of the polymer were determined as follows. First, the polymer was melted by heating, and then the molten polymer was rapidly cooled with dry ice. Next, using this polymer as the test specimen, the glass transition temperature (Tg) and melting point (Tm) of the polymer were determined using a differential scanning calorimeter (DSC) at a heating rate of 10 °C / min (heating mode).
[0164] [Methods for measuring the retardation, NZ coefficient, and slow axis direction of optical films]
[0165] The in-plane retardation Re, thickness-direction retardation Rth, NZ coefficient, and slow-axis direction of the optical film were measured using a phase difference meter (AxoScan OPMF-1 manufactured by AXOMETRICS).
[0166] [Evaluation of the flexibility of optical films]
[0167] A mandrel bending test was conducted using an optical film. Specifically, the optical film was bent to fit the mandrel diameter, and breakage was checked. If breakage occurred, the optical film was deemed unable to withstand the mandrel diameter. The mandrel bending test was conducted using mandrels with diameters of 6 mm, 3 mm, and 2 mm. The smallest mandrel diameter that allowed the optical film to remain intact was determined as the measured value. The smaller this measured value, the better the bendability of the optical film. If the optical film did not break at all in the mandrel bending test even when using a 2 mm diameter mandrel, the bendability measured value was "less than 2 mm".
[0168] [Manufacturing Example 1. Manufacturing of Crystalline Polystyrene]
[0169] In a 500 ml argon-purified glass container, 17.8 g (71 mmol) of copper sulfate pentahydrate (CuSO4·5H2O), 200 ml of toluene, and 24 ml (250 mmol) of trimethylaluminum were added, and the mixture was reacted at 40 °C for 8 hours. The solid fraction was then removed, yielding a solution. Toluene was then removed from the solution under reduced pressure at room temperature, yielding 6.7 g of the contact product. The molecular weight of this contact product was determined to be 610 by the freezing point depression method.
[0170] Next, 5 mmol of the above-mentioned contact product as aluminum atoms, 5 mmol of triisobutylaluminum, 0.025 mmol of trimethoxypentamethylcyclopentadienyltitanium, and 1 mmol of purified styrene were added to the reaction vessel, and polymerization was carried out at 90°C for 5 hours. Afterward, the catalyst components in the product were decomposed with a methanol solution of sodium hydroxide, and the product was repeatedly washed with methanol and dried to obtain 308 g of polymer (crystalline polystyrene).
[0171] The weight-average molecular weight (Mw) of the polymer was determined by gel permeation chromatography at 135 °C using 1,2,4-trichlorobenzene as solvent. The result showed that the weight-average molecular weight (Mw) of the polymer was 350,000. Furthermore, the melting point (Tm) and... 13 C-NMR analysis confirmed that the obtained polymer was crystalline polystyrene with an syndiotactic structure. The melting point (Tm) of crystalline polystyrene was 270 °C, and the glass transition temperature was 100 °C.
[0172] Repeat this process to prepare crystalline polystyrene with the syndiotactic structure required for evaluation.
[0173] [Manufacturing Example 2. Manufacturing of a crystalline polymer with positive intrinsic birefringence]
[0174] After thoroughly drying the metal pressure reactor, nitrogen replacement was performed. A 70% cyclohexane solution containing 154.5 parts cyclohexane, 42.8 parts dicyclopentadiene (with an endosome content of 99% or higher) (30 parts of dicyclopentadiene), and 1.9 parts 1-hexene was added to the metal pressure reactor, and the mixture was heated to 53°C.
[0175] A solution was prepared by dissolving 0.014 parts of tungsten tetrachloride benzoimide (tetrahydrofuran) complex in 0.70 parts of toluene. To this solution, 0.061 parts of a 19% diethoxyethylaluminum / n-hexane solution were added, and the mixture was stirred for 10 minutes to prepare a catalyst solution. This catalyst solution was added to a pressure reactor to initiate a ring-opening polymerization reaction. The reaction was then maintained at 53°C for 4 hours to obtain a solution of the ring-opening polymer of dicyclopentadiene. The number-average molecular weight (Mn) and weight-average molecular weight (Mw) of the obtained ring-opening polymer of dicyclopentadiene were 8750 and 28100, respectively, resulting in a molecular weight distribution (Mw / Mn) of 3.21.
[0176] In a solution of 200 parts of the obtained dicyclopentadiene ring-opening polymer, 0.037 parts of 1,2-ethylene glycol as a terminator were added, and the mixture was heated to 60°C and stirred for 1 hour to terminate the polymerization reaction. Then, 1 part of a hydrotalcite-like compound (manufactured by Kyowa Chemical Industry Co., Ltd., "kyoward (registered trademark) 2000") was added, and the mixture was heated to 60°C and stirred for 1 hour. Afterward, 0.4 parts of a filter aid (manufactured by Showa Chemical Industry Co., Ltd., "Radiolite (registered trademark) #1500") was added, and the adsorbent and solution were separated by filtration using a polypropylene pleated cartridge filter (PP Pleats Cartridge Filter) (manufactured by ADVANTEC Toyo Co., Ltd., "TCP-HX").
[0177] 100 parts of cyclohexane and 0.0043 parts of tris(triphenylphosphine)ruthenium carbonyl chloride were added to a solution of 200 parts of filtered dicyclopentadiene ring-opening polymer (polymer amount 30 parts). The mixture was subjected to a hydrogenation reaction at 6 MPa and 180°C for 4 hours. This yielded a reaction solution containing a hydride of the dicyclopentadiene ring-opening polymer. In this reaction solution, the hydride precipitates, forming a slurry solution.
[0178] The hydride contained in the above reaction solution was separated from the solution using a centrifuge, and dried under reduced pressure at 60°C for 24 hours to obtain 28.5 parts of a ring-opening polymer of dicyclopentadiene, a crystalline polymer with positive intrinsic birefringence. This hydride had a hydrogenation rate of over 99%, a glass transition temperature (Tg) of 93°C, a melting point (Tm) of 262°C, and a racemic-binary ratio of 89%.
[0179] [Example 1]
[0180] (1-1. Preparation of Crystalline Resin)
[0181] The syndiotactic crystalline polystyrene obtained in Manufacturing Example 1 was compounded at 295°C using a biaxial extruder to produce transparent crystalline resin particles.
[0182] (1-2. Extrusion film formation)
[0183] The granules of crystalline resin were melt-extruded using a hot melt extrusion film forming machine (Optical Control Systems' "Measuring Extruder Type Me-20 / 2800V3") with a T-die, and wound into rolls at a speed of 1.5 m / min to obtain a strip of raw material film approximately 120 mm wide, which serves as the resin film before solvent contact. The operating conditions of the film forming machine are described in sections below.
[0184] • Barrel temperature setting = 280℃~300℃
[0185] • Die head temperature = 300℃
[0186] Screw speed = 30 rpm
[0187] • Casting roll temperature = 80℃
[0188] The thickness of the raw material film is 25 μm. The retardation of the raw material film was measured at a measurement wavelength of 550 nm. The results showed that the in-plane retardation Re = 7 nm and the thickness retardation Rth = -10 nm.
[0189] (1-3. Solvent contact)
[0190] The raw material film described above was cut into 120mm × 120mm rectangles. These rectangular raw material films were then immersed in cyclohexane, the solvent, stored in a flat-bottomed square pan (vat), until the in-plane retardation Re = 58nm and the thickness retardation Rth = 111nm, yielding the pre-stretching film of the resin film after solvent contact. The pre-stretching film was removed from the cyclohexane, the cyclohexane adhering to the film surface was wiped off, and then it was allowed to air dry naturally. The thickness of the obtained pre-stretching film was 28μm.
[0191] (1-4. Stretching)
[0192] An intermittent biaxial stretching device (manufactured by ETO Co., Ltd.) was prepared. This stretching device includes an oven unit and stretching clamps for fixing the film. When using this stretching device, the film can be stretched by pulling it with the clamps inside the oven.
[0193] The pre-stretch film is cut into 100mm × 100mm rectangles. The two ends of each rectangle are clamped using the five clamps of the stretching device described above. The pre-stretch film is pulled using the clamps, and subjected to free uniaxial stretching along the length of the raw material film obtained in the extrusion film forming process. The stretching temperature is 130°C, and the stretching ratio is 1.3 times. Through this stretching, an optical film as a uniaxially stretched film is obtained.
[0194] The retardation of the obtained optical film was measured, and the results showed an in-plane retardation Re = 280 nm and a thickness direction retardation Rth = 5 nm. The slow axis of the optical film was perpendicular to the stretching direction. Furthermore, the NZ coefficient at a measurement wavelength of 550 nm was 0.52. The bendability of the obtained optical film was evaluated using the method described above.
[0195] [Example 2]
[0196] Change the linear speed in process (1-2) to change the thickness of the long strip of raw material film to 13μm.
[0197] In addition, in process (1-3), the impregnation time is adjusted to obtain a pre-stretched film with an in-plane delay Re = 33 nm and a thickness direction delay Rth = 56 nm, and the raw material film is impregnated in a solvent.
[0198] Apart from the above, the optical film was manufactured and evaluated using the same method as in Example 1.
[0199] [Example 3]
[0200] Change the linear speed in process (1-2) to change the thickness of the long strip of raw material film to 40μm.
[0201] In addition, in process (1-3), the impregnation time is adjusted to obtain a pre-stretched film with an in-plane delay Re = 24 nm and a thickness direction delay Rth = 45 nm, and the raw material film is impregnated in a solvent.
[0202] Furthermore, in process (1-4), the stretching ratio is changed to 1.1 times.
[0203] Apart from the above, the optical film was manufactured and evaluated using the same method as in Example 1.
[0204] [Comparative Example 1]
[0205] 1.1 parts of an antioxidant (tetra[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, manufactured by BASF Japan, "Irganox 1010") was mixed with 100 parts of the hydride of the dicyclopentadiene ring-opening polymer obtained in Manufacturing Example 2, and then fed into a biaxial extruder (Toshiba Machine Co., Ltd., "TEM-37B") with four die holes of 3 mm Φ. After the mixture of the hydride of the dicyclopentadiene ring-opening polymer and the antioxidant was formed into strands by hot melt extrusion molding, it was shredded by a wire cutter to obtain granules of crystalline resin.
[0206] The granules are used in process (1-2). In addition, the linear speed in process (1-2) is changed, and the thickness of the strip of raw material film is changed to 13 μm.
[0207] Furthermore, in steps (1-3), the solvent is changed to toluene. Then, the impregnation time is adjusted to obtain a pre-stretch film with an in-plane retardation Re = 10 nm and a thickness direction retardation Rth = -142 nm, and the raw material film is impregnated in the solvent.
[0208] Furthermore, the stretching temperature in process (1-4) is changed to 110℃, and the stretching ratio is changed to 1.2 times.
[0209] Apart from the above, the optical film was manufactured and evaluated using the same method as in Example 1.
[0210] [Comparative Example 2]
[0211] The raw material film was not impregnated in the solvent in process (1-3).
[0212] In addition, in process (1-4), the raw material film is stretched instead of the pre-stretched film, and the stretching temperature is changed to 110°C.
[0213] Apart from the above, the optical film was manufactured and evaluated using the same method as in Example 1.
[0214] [result]
[0215] The results of the above-described embodiments and comparative examples are shown in the table below. In the table below, the abbreviations have the following meanings.
[0216] SPS: Crystalline polystyrene.
[0217] Cy: Cyclohexane.
[0218] Tl: Toluene.
[0219] [Table 1]
[0220] [Table 1. Results of the Examples and Comparative Examples]
[0221]
[0222] [discuss]
[0223] In the embodiments, an optical film with an NZ coefficient greater than 0 and less than 1 was obtained. Therefore, in the embodiments, a refractive index nx1, n... satisfying equation (1) was obtained. y1 The optical film obtained in the examples uses crystalline polystyrene as a crystalline polymer with negative inherent birefringence, achieving in-plane birefringence Re / d that satisfies formula (2). Therefore, it is confirmed that optical films satisfying requirements (A) to (C) can be obtained according to the present invention.
[0224] In this embodiment, since the birefringence Rth / d in the thickness direction of the raw material film is different from that of the film before stretching, it can be seen that the refractive index of the raw material film changes upon contact with the solvent. Furthermore, in this embodiment, the in-plane retardation Re is sufficiently small compared to the in-plane retardation Rth in the thickness direction; therefore, it can be seen that the film before stretching satisfies equation (3), thus becoming a negative C-plate. The film before stretching obtained in this way has negative birefringence characteristics, and therefore, the aforementioned optical film can be obtained through stretching.
[0225] Compared to Comparative Example 2, which used the same materials, the Example underwent stretching at a high temperature. This was to effectively remove the solvent contained in the pre-stretch film of the Example through high temperature. Contact with the solvent increases the mechanical strength of the pre-stretch film, so even with stretching at such a high temperature, the film will not break.
Claims
1. An optical film formed solely from a crystalline resin comprising a crystalline polymer having inherent negative birefringence. The amount of the crystalline polymer having negative intrinsic birefringence in the 100% by weight of the crystalline resin is 90% by weight or more. The crystalline polymer with negative intrinsic birefringence is a crystalline polystyrene-based polymer, wherein the crystalline polystyrene-based polymer contains 83% by weight or more styrene-based units. The optical film has a single-layer structure. The refractive index nx1 of the optical film in the direction providing the maximum refractive index in the direction perpendicular to the thickness direction, the refractive index ny1 in the direction perpendicular to nx1 in the direction perpendicular to the thickness direction, and the refractive index nz1 in the thickness direction satisfy the following equation (1). The in-plane birefringence Re / d of the optical film satisfies the following equation (2). 。 2. The optical film according to claim 1, wherein, The optical film is a stretched film.
3. The optical film according to claim 1 or 2, wherein, The optical film has an elongated shape.
4. A polarizer having a polarizing film and an optical film according to any one of claims 1 to 3.
5. The polarizer according to claim 4, wherein, The slow axis of the optical film forms an angle of 80° to 100° with the absorption axis of the polarizing film.
6. A method for manufacturing an optical film, wherein the refractive index nx1 of the optical film, which provides the maximum refractive index in a direction perpendicular to the thickness direction, the refractive index ny1 in a direction perpendicular to nx1 in a direction perpendicular to the thickness direction, and the refractive index nz1 in the thickness direction satisfy equation (1). The manufacturing method includes the following steps: Step (i) involves preparing a pre-stretching film containing a crystalline polymer with negative intrinsic birefringence. as well as Step (ii): Stretch the pre-stretch film as described above; Process (i) includes: Prepare a resin film made solely of a crystalline resin containing a crystalline polymer with negative intrinsic birefringence; as well as The resin film is brought into contact with a solvent to obtain the pre-stretch film. The amount of the crystalline polymer having negative intrinsic birefringence in the 100% by weight of the crystalline resin is 90% by weight or more. The crystalline polymer with negative intrinsic birefringence is a crystalline polystyrene-based polymer, wherein the crystalline polystyrene-based polymer contains 83% by weight or more styrene-based units. The refractive index nx2 in the direction that provides the maximum refractive index in the direction perpendicular to the thickness direction, the refractive index ny2 in the direction perpendicular to nx2 in the direction perpendicular to the thickness direction, and the refractive index nz2 in the thickness direction of the above-mentioned pre-stretching film prepared in step (i) satisfy the following equation (3). 。 7. The method for manufacturing an optical film according to claim 6, wherein, The optical film has a single-layer structure.
Citation Information
Patent Citations
Production of styrene polymer
JP1987187708A
Laminated retardation plate and method of manufacturing the same
JP2003161833A
Optical compensation film and its manufacturing method
JP2006010812A
Optical film, polarizing plate, and in-plane switching mode liquid crystal display
WO2006117981A1